2013
DOI: 10.1007/s00436-013-3318-2
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPase EhRabB of Entamoeba histolytica is differentially expressed during phagocytosis

Abstract: It has been described that the pathogenicity of Entamoeba histolytica is influenced by environmental conditions and that transcription profile changes occur during invasion, suggesting that gene expression may be involved in the virulence of this parasite. However, the molecular mechanisms that are implicated in the control of gene expression in this microorganism are poorly understood. Here, we showed that the expression of the EhRabB protein, a small GTPase involved in phagocytosis, is modified through the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…However, these experiments proven slight changes in the amount of EhRabB protein (Figure ). In contrast to these results, other authors found that EhRabB protein diminished after 5 min of phagocytosis, and later, it augmented to almost reach the basal level (Hernandes‐Alejandro et al, ). Here, to obtain a better resolution in immunofluorescence assays, we drastically diminished the trophozoites: RBCs proportion.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, these experiments proven slight changes in the amount of EhRabB protein (Figure ). In contrast to these results, other authors found that EhRabB protein diminished after 5 min of phagocytosis, and later, it augmented to almost reach the basal level (Hernandes‐Alejandro et al, ). Here, to obtain a better resolution in immunofluorescence assays, we drastically diminished the trophozoites: RBCs proportion.…”
Section: Discussionmentioning
confidence: 62%
“…By this fact, we hypothesised that at least part of the complex is driven for degradation. In contrast, a part of EhRabB could be degraded by other pathways, as it was suggested by Hernandes‐Alejandro et al (). Interestingly, MVB‐like structures presented internal vesicles that could correspond to the intraluminal vesicles.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The Rab GTPase EhRabB, which is localized in cytoplasmic vesicles, is involved in the phagocytosis of E. histolytica [37, 38]. Rho family GTPases, including Rab proteins such as EhRabB, regulate the cytoskeleton and associated pathogenic processes such as phagocytosis, which in turn, is controlled by vesicular trafficking [39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the subcellular localization of Eh Rab21 during erythrophagocytosis was analyzed. Eh RabB is relocalized during the early steps of erythrophagocytosis from the cytoplasm to the plasma membrane (Hernandes‐Alejandro et al, ). In the case of Eh Rab21, it is not present in erythrocyte‐containing vesicles.…”
Section: Discussionmentioning
confidence: 99%